Understanding decision-making and health-seeking practices of the Hijra community in accessing informal healthcare services in Bangladesh: an exploratory qualitative study - Iftekhar, Yeasir Inzzamam (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2023.